Model Kompetensi Kepemimpinan pada Institusi Pendidikan Menengah Vokasi di Provinsi Kalimantan Barat - Nurmala, Nurmala (Vokasi: Jurnal Publikasi Ilmiah, 2023)
Leadership in an organization is the ability to deal with certain situations efficiently and effectively in influencing and controlling others in a way that leads to the achievement of organizational goals. Leadership in educational institutions, especially vocational secondary education, must be able to promote and stimulate creativity and prepare a cadre of quality teachers and students who can carry out intellectual production characterized by novelty and diversity, which can fully contribute to society. This has not been reflected in leadership practices in the vocational secondary education environment in West Kalimantan Province, which is indicated by differences in views so that some school principals implement leadership competencies with high professionalism, while others demonstrate weak leadership practices. Among these practices are a weak ability to build teams and collaborate, a weak ability to communicate, a weak ability to adapt, and a weak ability to motivate. This can be expected to be the result of the Principal being too focused on routine school work, including administrative tasks. This situation prompted research to be conducted to obtain theoretical and practical information about the leadership competency model applied in vocational secondary education institutions in West Kalimantan Province. The research was carried out using the path analysis method involving 55 respondents. The research results show that the leadership competency model in vocational secondary education institutions in West Kalimantan Province involves four main elements consisting of the ability to build teams and collaborate, the ability to communicate, the ability to adapt, and the ability to motivate. Communication skills, adaptability, and the ability to motivate simultaneously contribute 43.5% to the ability to build teams and collaborate. Other results from this research found that communication skills have a positive effect on the ability to build teams and collaborate with the Sig value. < 0.05. The implication of the results of this research is the need to increase the effectiveness of the communication skills of leaders in the vocational secondary education environment in West Kalimantan Province. Another implication of the results of this research is the need for further research to be carried out in the future to find other variables that were not examined in this research.